2019
DOI: 10.3390/ma12132210
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser Nano/Micro Textured Ti6Al4V Surfaces—Effect on Wetting and MG-63 Cell Adhesion

Abstract: Nano- and microstructured titanium surfaces have recently attracted attention in the field of regenerative medicine because of the influence which surface characteristics such as roughness and wettability can have on cellular processes. This study focuses on the correlation of surface properties (wettability and nano/micro texture) of laser-structured Ti6Al4V samples with pronounced cell adhesion. Samples were structured with multiple laser parameters in order to create a range of surface properties. Surface c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 51 publications
4
31
0
Order By: Relevance
“…The change in wetting behavior of laser irradiated areas on metals is consistent with findings of other research groups and is related to a change in the chemical composition of the surface over time [18,21,23,24]. Several studies have been published with explanatory approaches for the changes.…”
Section: Materials 2019 12 X For Peer Review 5 Of 11supporting
confidence: 87%
See 1 more Smart Citation
“…The change in wetting behavior of laser irradiated areas on metals is consistent with findings of other research groups and is related to a change in the chemical composition of the surface over time [18,21,23,24]. Several studies have been published with explanatory approaches for the changes.…”
Section: Materials 2019 12 X For Peer Review 5 Of 11supporting
confidence: 87%
“…The influence of femtosecond laser radiation on groove and lattice structures was presented in a work for a few strut widths [15], but no anisotropic droplet formation was displayed. Moreover, it is known that laser structured metallic surfaces show a strong dependency on the wetting behavior with regard to time and ambient atmosphere [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already shown that laser induced periodic surface structures (FLIPSS, LIPSS) provide favorable conditions for cell attachment [15,17,58,59]. The impact of two selected micro and two selected FLIPSS structures presented in the current study on the cell adhesion of MG-63 cells have already been investigated [15]. It could be demonstrated, that the osteoblasts adhered tightly, especially to the two investigated FLIPSS-structured surfaces, and it was found that the spreading was superior on these surfaces.…”
Section: It Can Be Deduced Frommentioning
confidence: 56%
“…An appropriate or relatively higher scanning line overlap leads to a homogenous distribution of nanostructures and helps avoid strong waviness of the laser treated surface. Several studies have already shown that laser induced periodic surface structures (FLIPSS, LIPSS) provide favorable conditions for cell attachment [15,17,58,59]. The impact of two selected micro and two selected FLIPSS structures presented in the current study on the cell adhesion of MG-63 cells have already been investigated [15].…”
Section: It Can Be Deduced Frommentioning
confidence: 70%
See 1 more Smart Citation